The Framing Of Muslim Women In Malay Drama Series - Sabihah Binti Shamsuddin
Malay dramas are consistent to be the popular option for day-to-day entertainment among the Malay community. However, the expansion of Malay drama industry nowadays seems to be in uncertain level in terms of its storyline creation, character building and so forth. In line with the Islamization in Malaysia, the Malay drama productions seemed as they left behind. Therefore, Islamic elements are applied in Malay dramas storyline as well as the characters nowadays, including the displaying of female characters that wcar hcadscarf. The featured characters seemed as they practicing the real teachings of Islam. The representation of Islam, especially the image of women characters wearing headscarf is used as an attraction for the audience to watch Malay dramas. However, there are studies showing that Malay dramas give negative impact towards the image of Islam. For that reason, this study has been conducted with the purpose to explore how Malay Muslim women are framed in Malay dramas and how suitable the character played with the Muslim women personality in terms of Islamic and Malay cultural views. In order to meet the research objectives, three Malay dramas were selected as the samples, they are Isteri Separuh Masa, Tahajjud Cinta and Suri Hati Mr. Pilot. This study applied content analysis as the research methodology. 13 episodes of lsteri Separuh Masa, 13episodes of Tahajjud Cinta and 16 episodes of Suri Hati MY.P ilot have been analyzed. These dramas were selected based on the characteristics of the main women characters which have the Islamic elements. The leading women characters in the three drama series were evaluated in terms of their visual depictions, personality attributes and interactions between the main women characters and other characters. The level of Islamicity and Malayness of each characters was identified and classified into three levels, which are high, intermediate and low level. As a result, the four leading women characters in the selected dramas does not show similar pattern in terms of Islamicity and Malayness. In overall, the level of Islamicity of these characters are in between high and intermediate level, while three of four characters are in intermediate level in terms of Malayness. Although the result are quite satisfying and do not require substantial improvements, there were portrayals in the dramas need to be reviewed. Related issues together with recommendations for improvement are also discussed.